Ethics, regulation, and beyond: the landscape of research with pregnant women - Carla Saenz; Phaik Yeong Cheah; Rieke van der Graaf; Leslie Meltzer Henry; Anna C. Mastroianni (BMC, 2017)
Abstract Scarce research with pregnant women has led to a dearth of evidence to guide medical decisions about safe and effective treatment and preventive interventions for pregnant women and their potential offspring. In this paper, we highlight three aspects of the landscape in which pregnant women are included or, more frequently, excluded from research: international ethics guidance, regional and national regulatory frameworks, and prevailing practices. Our paper suggests that, in some cases, regulatory frameworks can be more restrictive than international ethics guidance, and that even when regulations permit research with pregnant women, practical challenges-as well as the prevailing practices of stakeholders, such as ethics review committees and investigators-may lead to the generalized exclusion of pregnant women from research.